Transformasi Manajemen Pembelajaran Dalam Meningkatkan Mutu Lembaga Pendidikan Dasar Islam - Ismail, Ahmad Nur; Tifliya, Fenti Mamluatut; Khoiriyah, Miftakhul; Tamwifi, Irfan; Abitolkha, Amir Maliki (Universitas Islam Negeri Raden Intan Lampung, 2021)
The purpose of this study was to determine the transformation model of learning management at Roushon Fikr Islamic Elementary School (SDI) Jombang in improving the quality of the institution. The locus of this research was taken, because SDI Roushon Fikr is an Islamic educational institution that was present in the era of the industrial revolution 4.0, and is located in the santri city of Jombang as the basis of a large Islamic boarding school in East Java. The research method used is a qualitative descriptive approach, with data mining techniques through observation, interviews, and relevant documentation as secondary data. The results showed that; first, learning planning at SDI Roushon Fikr is carried out by teachers, starting from the process of preparing lesson plans (RPP), syllabus, and learning tools that are adjusted to the educational calendar and effective week; second, the organization of learning at SDI Roushon Fikr is carried out by representatives of the school in the field of curriculum, through the stage of division of responsibilities for each teacher that is relevant to the field of expertise of each teacher; third, the implementation of learning at SDI Roushon Fikr, starting with opening activities, core activities, and closing activities; fourth, monitoring and evaluation of learning is carried out by the principal through supervision activities for school representatives in the curriculum and subject teachers.